PENGUJIAN BEBERAPA PERANGKAP HAMA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) Oryctes rhinoceros Linn. - Tri Yanita Ginting (Universitas Pembangunan Panca Budi, 2020)
The decline in the production of oil palm yields in the village of Tomuan Holbung,the sub-district of Bandar Pasir Mandoge, was identified as a result of the very high spread ofpests. Pests that are often found one of them is a type of rhino beetle pest (Oryctes rhinocerosLinn.). The purpose of this study is to find out what traps are more effective in controllingOryctes rhinoceros Linn pests and also to get a comparison of the interests of Oryctesrhinoceros Linn based on sex to some trap treatments. The use of traps to be tested onOryctes rhinoceros Linn are: 1) traps in yellow color (W0), 2) traps with pheromones (W1),3) traps in yellow color and pheromones (W2). The parameters observed in this study werethe population of Oryctes rhinoceros Linn who were attracted to the traps observed 2 daysafter laying the traps (2 HSA) for 4 weeks and the population of Oryctes rhinoceros Linncaught by male or female sex. The results showed that the highest number of catches ofOryctes rhinoceros Linn was found in the treatment of yellow and pheromone (W2) traps,namely 25 insects with an average population of imago trapped at 6.25 insects / month (± 6insects / month ). Then followed successively by trapping treatment with pheromones (W1)as many as 19 insects with an average trapped imago population of 4.75 insects / month (± 5insects / month) and trap treatment with yellow (W0) as many as 6 insects with an averagepopulation of imago trapped by 1.5 insects / month (± 2 insects / month). While the catches ofmale and female Oryctes rhinoceros Linn imago based on the sex of male and femaleobtained results that the female Imago Oryctes rhinoceros Linn was more numerous than themale Imago Oryctes rhinoceros Linn trapped because female imago were more interested andrecognized molecules from synthetic aggregation pheromones (Ethyl 4-methyloctanoate).Keywords : Traps, Colors, Pheromones, Oryctes rhinoceros Linn, Palm Oil.